2021
DOI: 10.1016/j.jcot.2021.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proprioceptive exercises and strengthening on pain and functionality for patellofemoral pain syndrome in women: A randomized controlled trial

Abstract: Objective: The objective of this study was to verify the effects of resisted and proprioceptive exercises program for the treatment of patients diagnosed with patellofemoral pain syndrome (PFPS). Design method: Randomized Controlled Trial e level of evidence, II. Methods: Sixty female patients, clinically diagnosed with PFPS, were allocated into two experimental groups. The exercise group (ExG) underwent 6 weeks of a resisted and proprioceptive exercises for the trunk muscles, abductors and lateral hip rotator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“… Risk of bias: The mean PEDro score was 3.6 (1.8), with 50% presenting low RoB ( n = 7), 14% moderate RoB ( n = 2), and 36% presenting high RoB ( n = 5) (Additional file 6 ). Pain data (14 studies [ 28 , 31 , 32 , 61 , 107 , 113 , 114 , 122 128 ] ): low-level evidence indicated that balance interventions were largely effective to improve pain compared to non-balance interventions (SMD 0.82, 95% CI 0.30–1.33, Fig. 15 and Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Risk of bias: The mean PEDro score was 3.6 (1.8), with 50% presenting low RoB ( n = 7), 14% moderate RoB ( n = 2), and 36% presenting high RoB ( n = 5) (Additional file 6 ). Pain data (14 studies [ 28 , 31 , 32 , 61 , 107 , 113 , 114 , 122 128 ] ): low-level evidence indicated that balance interventions were largely effective to improve pain compared to non-balance interventions (SMD 0.82, 95% CI 0.30–1.33, Fig. 15 and Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Egger’s test was not significant for publication bias ( p = 0.054); however, as we found a marginal p value, we performed the sensitivity analyses which showed different results. Trim-and-fill analysis indicated that balance interventions have no effect on pain (low-level evidence, SMD 0.38, 95% CI − 0.28–1.03; Table 3 ) and the analysis by removing the outliers [ 61 , 125 , 128 ] indicated that balance interventions have a small effect in improving pain in people with PFP compared to non-balance interventions (low-level evidence, SMD 0.40, 95% CI 0.04–0.76; Table 3 ) (Additional file 3 ). Subgroup and meta-regression analyses did not indicate possible sources of heterogeneity (Additional file 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A SDPF é caracterizada por uma dor na região anterior do joelho, da região retropatelar ou peripatelar. Tendo como consequência crepito, instabilidade da marcha e dores na articulação do joelho, dificultando ações como a flexão, agachamento, subir e descer escadas e após longos períodos de repouso (Clifford, et al, 2022;Silva, et al, 2021;Ferreira, et al, 2020).…”
Section: Introductionunclassified